2020
DOI: 10.1002/cctc.201902324
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Porous Carbon Cages for Electrocatalytic Reduction of Oxygen: Enhanced Performance with Iron and Cobalt Dual Metal Centers

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) data were interpreted by analyzing the results obtained in the literature. [66][67][68][69][70][71][72][73] The survey spectra of Fe, Fe-Co, Ni-Co, and Ni-Fe-based electrocatalysts, treated at 600 or 900 • C, are shown in (Figure S1A-C) chiefly indicating the presence of carbon, nitrogen, oxygen, and metals. The unmarked peaks at 315 and 560 eV are related to the shake-up lines of C1s and N1s signals, respectively, whereas the other tiny and narrow peaks between C1s and N1s regions correspond to a low amount (<0.3%) of potassium and calcium, mainly addressed to litchi residuals.…”
Section: Characterization Of Litchi Electrocatalystsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) data were interpreted by analyzing the results obtained in the literature. [66][67][68][69][70][71][72][73] The survey spectra of Fe, Fe-Co, Ni-Co, and Ni-Fe-based electrocatalysts, treated at 600 or 900 • C, are shown in (Figure S1A-C) chiefly indicating the presence of carbon, nitrogen, oxygen, and metals. The unmarked peaks at 315 and 560 eV are related to the shake-up lines of C1s and N1s signals, respectively, whereas the other tiny and narrow peaks between C1s and N1s regions correspond to a low amount (<0.3%) of potassium and calcium, mainly addressed to litchi residuals.…”
Section: Characterization Of Litchi Electrocatalystsmentioning
confidence: 99%
“…Moreover, the desorption of *OH, which was the rate‐determining step, was also facilitated by the coexistence of FeN 5 and SeC 2 dual active sites. Mercado et al [ 66 ] synthesized a DAC with Fe and Co dual‐metal atoms embedded into nitrogen‐doped porous carbon cages (CHS–FeCo) by controlled pyrolysis of silica nanoparticle–supported melamine–formaldehyde resin embedded with iron and cobalt precursors, followed by acid etching. The CHS–FeCo exhibited an impressive ORR performance with E onset = +0.93 V and E ½ = +0.79 V. Repeated potential sweeping showed that the polarization curves of CHS–FeCo remained virtually unchanged for up to 10 000 cycles, due to the strong incorporation of the metal centers into the carbon skeletons.…”
Section: Electrocatalytic Performancesmentioning
confidence: 99%
“…[8,[20][21][22][23] Fe/NÀ C electrocatalysts have been widely developed as ORR electrocatalysts to fulfil the demands. [24][25][26][27][28] In recent years, single-atom catalysts (SACs) possessing high atomic utilization efficiency and unique distinct properties have been developed. [13,[29][30][31][32][33][34][35] Owing to the unique structural characteristics, SACs exhibit high activity and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal‐based catalysts, such as transition metal (M), nitrogen (N) co‐doped carbons (M/N−C), have attracted attentions due to the high activity and the low cost [8,20–23] . Fe/N−C electrocatalysts have been widely developed as ORR electrocatalysts to fulfil the demands [24–28] …”
Section: Introductionmentioning
confidence: 99%